Development and validation of a HPLC-UV method for determination of Proscillaridin A in Drimia maritima - M. Bozorgi; Gh. Amin; S. Kasebzade; M. Shekarchi (Iranian Society of Pharmacognosy, 2016)
Background and objectives:Drimia maritima (L.) Stearn also known as squill is a medicinally important plant that has been used for various ailments such as dropsy, respiratory disorders, jaundice and epilepsy from ancient times. Proscillaridin A is identified as one of the most effective compounds in the plant with remarkable pharmacological features including efficacy against congestive heart failure, antitumor, t-cell suppressive and analgesic activities. In the present study, a reliable high performance liquid chromatography (HPLC) method has been developed for quantification of proscillaridin A in D. maritima.  Methods: The separation of compounds was performed using gradient elution (methanol: water) on a reversed phase ACE C18 with flow rate of 1 mL/min and UV detection at 300 nm for 50 min. The method was evaluated using validation parameter such as selectivity, linearity, precision, recovery, limit of detection (LOD) and limit of quantization (LOQ). Results: The separation technique was selective for quantification of proscillaridin A. The calibration graph was linear with r2> 0.998. The intra and inter-day precision (RSD%, 3.8-4.16 and 7.5) were satisfactory. LOD and LOQ were calculated as 0.6 and 1.8 µg/mL respectively. The recovery average was 93.7%. Conclusion: Due to precision, accuracy and speed, the proposed HPLC-UV method could be applied for determination of proscillaridin A in Drimia maritima samples.